The importance of a global mindset to the Malaysian food industry SMEs / Nurul Ulya Abdul Rahman and Norziani Dahalan@Omar - Abdul Rahman, Nurul Ulya; Dahalan@Omar, Norziani (UiTM Cawangan Kedah, 2022)
The food industry in Malaysia is a major contributor to Malaysia's economic growth even during the pandemic or economic crisis. It provides numerous opportunities, particularly for the Small and Medium Enterprise (SMEs): (1) increasing business efficiency; (2) enhancing product quality; (3) increasing production productivity, profit, and market share; (4) strengthening Bumiputera (native) SME networking; (5) generating competitive advantage. However, there are several challenges for this industry to remain competitive in the local market. Previous studies have revealed that internationalization strengthens SMEs competitiveness and survival prospects. Thus, for SMEs of the food industry to maintain their business growth and sustainability, they should involve in the international business transaction through accessing third markets by exporting, investing abroad and licensing. There are numerous discussions on the internationalization aspect of SMEs that require them the capability to develop international performance, which includes global mindset. Global mindsets from the aspect of global leadership are crucial in overcoming barriers to the internationalization, such as increasing the number of skillful workers in Malaysia. Additionally, the cost of hiring professional and skillful workers is a constraint for smaller companies to resolve with less financial resources compared to the multinational companies. Therefore, this study is aimed to improve the Malaysian food industry SMEs' performance at an international level. This research applied a quantitative approach and involved hypothesis testing on the relationship between global mindset and international performance. A cross-sectional study was utilized to collect the data required for the hypothesis testing by using questionnaire method representing Malaysian participants' view on internationalization of SMEs.